Selective ion permeation involves complexation with carboxylates and lysine in a model human sodium channel - Flood, Emelie (PLoS Comput Biol, 2018)
Bacterial and human voltage-gated sodium channels (Na(v)s) exhibit similar cation selectivity, despite their distinct EEEE and DEKA selectivity filter signature sequences. Recent high-resolution structures for bacterial Na(v)s have allowed us to learn about ion conduction mechanisms in these simpler homo-tetrameric channels, but our understanding of the function of their mammalian counterparts remains limited. To probe these conduction mechanisms, a model of the human Na(v)1.2 channel has been constructed by grafting residues of its selectivity filter and external vestibular region onto the bacterial Na(v)Rh channel with atomic-resolution structure. Multi-μs fully atomistic simulations capture long time-scale ion and protein movements associated with the permeation of Na(+) and K(+) ions, and their differences. We observe a Na(+) ion knock-on conduction mechanism facilitated by low energy multi-carboxylate/multi-Na(+) complexes, akin to the bacterial channels. These complexes involve both the DEKA and vestibular EEDD rings, acting to draw multiple Na(+) into the selectivity filter and promote permeation. When the DEKA ring lysine is protonated, we observe that its ammonium group is actively participating in Na(+) permeation, presuming the role of another ion. It participates in the formation of a stable complex involving carboxylates that collectively bind both Na(+) and the Lys ammonium group in a high-field strength site, permitting pass-by translocation of Na(+). In contrast, multiple K(+) ion complexes with the DEKA and EEDD rings are disfavored by up to 8.3 kcal/mol, with the K(+)-lysine-carboxylate complex non-existent. As a result, lysine acts as an electrostatic plug that partially blocks the flow of K(+) ions, which must instead wait for isomerization of lysine downward to clear the path for K(+) passage. These distinct mechanisms give us insight into the nature of ion conduction and selectivity in human Na(v) channels, while uncovering high field strength carboxylate binding complexes that define the more general phenomenon of Na(+)-selective ion transport in nature.